Case Report: Secukinumab for the treatment of severe psoriasis in a patient with hereditary hemochromatosis - Yu, Yingzhe; Lu, Lingyi; Fan, Xin; Wang, Sihan; Lin, Bingjiang (Frontiers in Medicine, 2025)
There are several comorbidities associated with psoriasis, including genetic disorders such as hereditary hemochromatosis, which can lead to organ damage secondary to iron overload. Herein, we report the case of a 38-year-old Chinese man with hereditary hemochromatosis who received secukinumab for the treatment of severe psoriasis. Follow-up after 3 months showed that the patient’s lesions had almost resolved and remained well-controlled for 2 years without any reported side effects. Patients with psoriasis and hereditary hemochromatosis have limited treatment options due to the effects of iron overload on the liver, particularly because it may increase the risk of hepatocellular carcinoma. Interleukin-17A (IL-17A) inhibitors, such as the secukinumab used in this case, may benefit these patients.